Analisis Yuridis Terhadap Perubahan Perjanjian Sertifikat Tanah Secara Sepihak yang Dilakukan Kreditur (Studi Putusan No. 235/Pdt.G/2020/PN Sgr) - Az zahra, Lutfiyyah; Andryan (LPPM Universitas Ekasakti Padang, 2024)
This research aims to analyze juridically the unilateral changes to land certificate agreements carried out by creditors (study decision No. 235/Pdt.G/2020/Pn Sgr). This research uses normative legal research methods with a normative juridical approach. Research data was obtained from primary legal materials (No. 235/Pdt.G/2020/Pn Sgr) and secondary legal materials (laws, statutory regulations, legal books, and scientific articles). The data collection technique was carried out by means of document study. The collected data was then analyzed qualitatively using deductive and inductive methods. The results of this research are to punish the debtors to hand over the Title Certificates while they are still in the owner's name if the creditors have made payment of their obligations to the debtors as financiers of their debts and receivables in the amount of Rp. 250,000,000,- (two hundred and fifty million rupiah) with details of the principal debt amounting to Rp. 150,000,000,- (one hundred and fifty million rupiah) plus loan interest amounting to Rp. 100,000,000,- (one hundred million rupiah), The judge also rejected the creditor's lawsuit against the debtor who asked for compensation of IDR 1,550,000 (One Billion Five Hundred and Fifty Million) which was borne jointly by the debtors.